Extraction, Characterisation And Application Of Agar From Gracilaria Sp - Wongsuban, Benchamaporn (1999)

(untitled)
The methods for extraction of agar from seaweeds differed either in the type of extraction solution, its concentration, the heating temperature or heating time used. Alkali pre-treatment of the seaweeds has also been performed in order to improve the agar gel strength. Sodium hydroxide has been used and the conditions were varied in terms of sodium hydroxide concentration, soaking temperature and time. In this study, the optimum conditions for extraction of agar from Gracilaria sp. were determined. The characteristics of the extracted agar were then compared with that of conumercial agar and the behaviour of the agar in roselle jelly was also determined. The three species of Gracilaria used in this study were Gracilaria changii, Gracilaria fisheri and Gracilaria tenuistipitata. Agar was extracted from the seaweeds using different extraction solutions. They were distilled water, sulphuric acid, acetic acid and sodium hexametaphosphate. The concentrations of sulphuric acid and acetic acid were in the range of 0.005-0.03% while the concentrations of sodium hexametaphosphate were in the range of 0.0005-0.003 M.